Interferon-γ, interleukin-10 and interferon-inducible protein 10 (CXCL10) as serum biomarkers for the early allograft dysfunction after liver transplantation - Karakhanova, Svetlana; Bazhin, Alexandr V.; Werner, Jens (Transplant immunology, 2016)
Orthotopic liver transplantation (LTP) is nowadays a standard procedure, and provides the chance of survival of patients with end-stage non-treatable chronic liver disease or acute liver failure. Despite long-term survival with a good quality of life in the majority of patients, about 20% develop early allograft dysfunction (EAD), which leads to death or the need for re-transplantation. Therefore, the early diagnosis of EAD and evaluation of its risk factors are very important. Many primary pathological processes leading to EAD are accompanied by the release of different mediators and by a change of biochemical parameters detectable in the peripheral blood. The aim of this study was to investigate cytokines as well as soluble mediators in the serum of patients with and without EAD from our LTP bank, and to evaluate their predictive and prognostic values for EAD. We demonstrated for the first time that the level of IFNγ during the nearest preoperative period may serve as a predictive parameter for EAD. We additionally found that IL-10 and CXCL10 (IP-10) levels in the early postoperative period can be prognostic for EAD. We believe our data expand the spectrum of predictive and prognostic parameters for EAD in LTP.
Gesehen am 22.10.2019
Available online 4 December 2015